A REVERSE CHILD PROTAGONISM: AN ANALYSIS ON LEGAL PROTECTION AGAINST CHILD LABOR IN BOLIVIA - Bueno da Rosa Moreira, Rafael; Viana Cus´tódio, André (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2021)
The main objective is to analyze the legal protection against child labor in Bolivia since the approval of the reduction of the legal working age by the "Código del Niño, Niña y Adolescente" that was supported by the social movement called Unión de Niños, Niñas y Adolescentes Trabajadores de Bolivia (UNATSBO). The guiding problem is the analysis on how the legal protection of human and fundamental rights related to the confrontation of child labor and the protagonism of children and adolescents in Bolivia has been guaranteed since the minimum working age was lowered. Concerning the problem solving, the specific objectives were verifying the universal foundations in Convention on the Rights of the Child of the United Nations, which links the legal system of Bolivia; demonstrating international legal protection against child labor within the framework of the International Labor Organization; and analyzing the reduction of the minimum working age and the participation of the Unión de Niños, Niñas y Adolescentes Trabajadores de Bolivia (UNATSBO) in this process. The approach method is the deductive and the method of procedure is the monographic, using bibliographic research techniques. As a result, it is noted that the reduction of the minimum working violates the ratified international conventions and constitutional clauses, damaging the integral development of children and adolescents, justifying the declaration of unconstitutionality of the Article 129 of the “Código del Niño, Niña y Adolescente” by the Plurinational Constitutional Court of Bolivia. Furthermore, it is a social backlash and flexibilization of human and fundamental rights.